Information technology in disaster risk reduction : first IFIP TC 5 DCITDRR International Conference, ITDRR 2016, Sofia, Bulgaria, November 16-18, 2016, Revised selected papers /: first IFIP TC 5 DCITDRR International Conference, ITDRR 2016, Sofia, Bulgaria, November 16-18, 2016, Revised selected papers. (2017) - Unknown
No abstract available